The Effect of Teaching Physics by Using the 5E Learning Cycle Based on the Learning Management System "Blackboard" and interactive multimedia program on the Achievement of Engineering Students at King Saud University - Sawaftah , Walid; Rudwan, Moustafa (Jordan Journal of Educational Sciences, 2014)
This study aimed to investigate the effect of teaching physics by using the 5E learning cycle based on the learning management system "Blackboard" and interactive multimedia program on the achievement of engineering students at King Saud University in Saudi Arabia, in comparison with the traditional method. The study sample consisted of 50 engineering students at King Saud University who were divided into three groups: the first group (19 students) studied physics by using the 5E learning cycle based on the learning management system Blackboard; the second group (15 students) studied the same content by using the 5E learning cycle based on interactive multimedia program; and the third group (16 students) studied the same content by using the traditional method. The analysis results of (ANOVA) for the students’ scores on the achievement test indicated that the first and second groups significantly outperformed the third group, and the first group significantly outperformed the second group. Finally, based on these findings, some of recommendations are presented